Resistance of vigna unguiculata to Liriomyza sativae - Moraes, Gilberto J. de; Magalhães, Arnóbio A. de; Oliveira, Carlos A.V. (Pesquisa Agropecuaria Brasileira, 2014)
The resistance of 50 varieties of Vigna unguiculata Walp to the attack of Liriomyza sativae Blanchard was studied under furrow irrigation. The varieties suffering the least and the most damages due to the insect were VITA-3 and 5F=-PI-112, respectively. There was an intermediary susceptibility of the studied varieties between those two extremes.